2021
DOI: 10.1007/s12649-021-01613-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fuels and Effluents Originating from Washing and Hydrothermal Carbonisation of Residual Biomass

Abstract: A series of four different biomass feedstock was washed and hydrothermally carbonized at temperatures of 50 °C and 150–270 °C for four hours, respectively. For the first time both the resulting solid and liquid products were characterised and evaluated in a comprehensive study. Concerning fuel properties, HTC had a higher impact on the fuel quality than washing. HTC yielded hydrochar with higher carbon content than the starting material leading to a significant increase in heating value, while washing only had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…These results clearly show that large increases in the reactor size and the amount of feed do not have an effect on the hydrothermal carbonization process. The obtained values are slightly lower than previously reported solid yields for the HTC of olive pomace (55-75%) [9,26,35,[42][43][44][45][46], which could be a result of the high moisture content of the applied reaction mixture. The small-scale screening study with orange peels showed that the orange peels (milled into small pieces) could not be used as received, as this feedstock could not be stirred.…”
Section: Batch Experimentscontrasting
confidence: 72%
See 2 more Smart Citations
“…These results clearly show that large increases in the reactor size and the amount of feed do not have an effect on the hydrothermal carbonization process. The obtained values are slightly lower than previously reported solid yields for the HTC of olive pomace (55-75%) [9,26,35,[42][43][44][45][46], which could be a result of the high moisture content of the applied reaction mixture. The small-scale screening study with orange peels showed that the orange peels (milled into small pieces) could not be used as received, as this feedstock could not be stirred.…”
Section: Batch Experimentscontrasting
confidence: 72%
“…Another benefit of water as the reaction medium is the removal of many water-soluble alkali metals and salts from the solid phase. This significantly enhances the combustion behavior of the hydrochar solid product, according to reduced slagging and corrosion at an elevated temperature, due to the reduction in the potassium and chlorine content [11,26,27]. In the past years many application studies have been performed on hydrochar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the best fit for ash yield (Figure 5) was achieved using a 2nd-order polynomial. Moreover, the polynomial reaches values close to 1.0 at temperatures below 100 • C. This seems sensible since Y a < 1 indicates that a part of the inorganic content of raw biomass was washed out during the treatment, and it has been reported in the literature that washing biomass with hot water can remove a part of its ash [90,91].…”
Section: Hydrothermal Carbonization-process Performance and Effect Of...mentioning
confidence: 59%
“…Moreover, the polynomial reaches values close to 1.0 at temperatures below 100 °C. This seems sensible since Ya < 1 indicates that a part of the inorganic content of raw biomass was washed out during the treatment, and it has been reported in the literature that washing biomass with hot water can remove a part of its ash [90,91]. Energy yields, shown in Figure 4, are higher than respective mass yields, which is caused by the fact that Y e is the result of the multiplication of Y m by respective energy densification ratio (ED) [85,86].…”
Section: Hydrothermal Carbonization-process Performance and Effect Of...mentioning
confidence: 99%